Effect of coral Goniopora Sp scaffold application on human osteoblast-like MG-63 cell activity in vitro - Julia, Vera; Abbas, Basril; Bachtiar, Endang W; Latief, Benny S; Kuijpers-Jagtman, Anne M (UI Scholars Hub, 2019)
Background: Coral is an osteo-conductive biomaterial that can act as an alternative scaffold for osteogenesis. In this in vitro study we analyzed the activity of osteoblast-like cells after treatment with the coral Goniopora. Methods: Human osteoblast-like MG-63 cells were incubated in α-minimal essential medium supplemented with 10% fetal bovine serum and 300 ng/mL amphotericin B plus 1% penicillin-streptomycin and stored in a 5% CO2 incubator at 37°C. The Goniopora were smashed into size A (20 mesh), B (1–2 mm), and C (200 mesh) particles, sterilized using gamma radiation and applied to cells. Protein and alkaline phosphatase (ALP) concentrations were evaluated after incubation for 24 and 48 h. Results: The protein assay of 24 h and 48 h cultured osteoblasts illustrated that treated cells, whether with coral size A, B and C exhibited a lower mean value compared to the untreated cells. For ALP levels there were statistically significant differences at 48 h between B and C (p = 0.004), and A and C (p = 0.09). Conclusions: No significant differences in total protein concentrations were found among all groups after 24 and 48 h. Smaller coral size and longer incubation time tended to facilitate osteogenesis. These results require further empirical validation.